Révue systématique de l'expérience des prestataires dans la facilitation des sessions prénatales en groupe - Jalana Lazar; Laura Boned-Rico; Ellinor K. Olander; Christine McCourt (BMC, 2021)
Plain language summary Receiving antenatal care in a group setting has been found to be safe and satisfying for women and is supported by international public health guidelines. However, questions remain about the experience of health care professionals tasked with providing this model, such as whether they like working in this model and whether they support its expansion. To answer these questions, the team searched for studies about the experiences of health care providers with group antenatal care, and only included those studies where providers themselves spoke about their own experiences of providing this kind of care. Our review demonstrated that midwives, doctors, nurses and community health workers mostly enjoyed facilitating group antenatal care. They particularly appreciated the ability to give women the kind of care they felt women want and need. Health care providers also experienced some changes in their professional roles, in relation to both the women they serve and their colleagues and organizations. In order to determine if group antenatal care models are a satisfying and sustainable option for health care professionals in the long term, more research is needed.